2023
DOI: 10.3390/nu15081915
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in the Association between Serum Vitamin E Levels and Depressive Symptoms: Korea National Health and Nutrition Examination Survey

Abstract: Studies have reported inconsistent results regarding the relationship between serum vitamin E levels and depressive symptoms. Furthermore, the potential modulating role of age and sex has been underexplored. We conduct an age- and sex-stratified investigation of the association between serological vitamin E status and depressive symptoms in a large nationwide sample. Data from the Korean National Health and Nutrition Examination Survey were analyzed (n = 4448). The participants were stratified into four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Obesity and diabetes mellitus were positively associated with depression in premenopausal women, and stroke and myocardial infarction were positively associated with depression in menopausal women. Studies of the association between serum vitamins and depression in Asian subjects are rare [6,7]. Previous studies in Western populations have generally reported that vitamin A levels are positively associated with depression [5,[21][22][23] and that vitamin E and vitamin B9 levels are negatively association with depression [8,10,11,[24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and diabetes mellitus were positively associated with depression in premenopausal women, and stroke and myocardial infarction were positively associated with depression in menopausal women. Studies of the association between serum vitamins and depression in Asian subjects are rare [6,7]. Previous studies in Western populations have generally reported that vitamin A levels are positively associated with depression [5,[21][22][23] and that vitamin E and vitamin B9 levels are negatively association with depression [8,10,11,[24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The link between oxidative stress and depression has been explored [6]. Folate is involved in the synthesis of neurotransmitters such as serotonin, which plays a key role in the regulation of mood [5,7]. Because the serum levels of vitamins A, E, and B9 were presented in the Korea National Health and Nutrition Examination Survey (KNHANES) data from 2016 to 2018, we selected vitamins A, E, and B9 among the several types of vitamins.…”
Section: Introductionmentioning
confidence: 99%